THE DOCTRINAL OBJECTIVES IN THE HADITHS OF MULTIPLICATION OF GOOD DEEDS: SELECTED EXAMPLES FROM SAHIHAIN - Yaser Mansour Mohammed (Islamic Sciences Journal, 2025)
ll praise is due to Allah, Lord of the Worlds, the One and Only in His Oneness, Who guides whom He wills to His straight path. May blessings and peace be upon the noblest of Prophets and Messengers, our Master and Intercessor Muhammad, and upon his family and all his companions. This research addresses the doctrinal objectives derived from the prophetic hadiths that indicate the multiplication of good deeds, which are mentioned in the two Sahihs of Al-Bukhari and Muslim. The study selects specific examples of these hadiths, analyzing and discussing their content, highlighting their doctrinal dimensions and the faith-based meanings they contain, and employing them to enhance the correct doctrinal understanding for the Muslim individual. The study aims to serve both worldly and hereafter interests of the believers, demonstrating how the multiplication of rewards contributes to deepening conviction in Allah, strengthening belief in His Names and Attributes, reinforcing certainty in the Hereafter, and cultivating fear and love of Allah Almighty. This, in turn, motivates the Muslim to perform righteous deeds sincerely for Allah’s sake. For this purpose, the research is entitled: “The Doctrinal Objectives in the Hadiths of Multiplication of Good Deeds – Selected Examples from Sahihain”.The research plan comprises three sections: The first section: defines the terms of the title. The second section: addresses the multiplication of good deeds based on specific timeframes. The third section: addresses the multiplication of good deeds based on location and conditions.